Dinâmica biogeoquímica do estuário do Rio Itajaí-Açú, SC - Pereira Filho, Jurandir (2006)
The Itajaí river estuary, SC, is located in the final portion of Itajaí river watershed, which has a total area of about 15,500 km2. The terminal region of this watershed is characterized by the presence of important cities such as Blumenau and Itajaí. Agriculture is also important, specially irrigated rice culture. The aim of this study was to evaluate the spatial-temporal variability of water quality and the nutrient transport and transformation processes in the estuary. A weekly monitoring was carried out from october/2003 to december/2004, along seven estuarine sampling stations, one station in the Itajaí-Mirim river (the main tributary) and one reference station located in a undisturbed area. Activities included measurements of salinity, pH, dissolved oxygen, temperature and nutrients (NH4 +, NO2 -, NO3 -, PO4 3-, H4SiO4), biochemical oxygen demand (BOD), total and organic phosphorus (TP and DOP), particulate organic carbon (POC), suspended particulate material (SPM) and chlorophyll-a (Cla). The intratidal nutrient variations was also evaluated in the middle and low estuary, in december/1999. This survey included hourly measurements of the stream velocity, water level, SPM and nutrients in three fixed stations, during 25 hours (2 tidal cycles). Multivariate analysis showed that the main forcing factors causing the system variability were the river discharge, the marine influence, the urbanization and the rice culture. It was proposed that the system can be divided in riverine limit, and high, middle and low estuary. The urbanization was responsible by the spatial variation of the water quality, showing increases in the organic matter (BOD, NH4 +, POC and DOP) and progressive decrease of dissolved oxygen. Despite the effect of dilution by the marine waters, increasing in NH4 + was detected in the low estuary, which is probably related to the urban organic loads and the fisheries processing plants effluents. When the river discharge was low during a long time, increasing in NH4 + and NO2 - and severe decreasing in dissolved oxygen was observed. This situation could be an early indication of hypoxia in the estuary. River discharge increasing resulted in increased SPM, TP, NO3 - and Si. This trend was intensified by high soil exposition in the beginning of the rice culture cycle. In this period there was a decreasing in Si, suggesting influence of rice culture Si uptake. The nutrient budget showed that 50% of PO4 3- input was shifted in the middle and low estuary. This was probably related to adsorption to SPM, once chlorophyll-a in the estuary was relatively low. The non-conservative increase of NH4 + in the low estuary suggest a heterotrophic behavior, once the organic load and turbidity were generally high. The intratidal variation of nutrients showed to be lower than other regional estuaries and also seemed to be influenced by the surrounding area. The tendency of non-conservative increase of NH4 + was also evident and related to salinity values between 5 and 15, which occurred during the water mixing inside the estuary.